CRYOSURGERY FOR TREATMENT OF CUTANEOUS WARTS - Adhi Paramitha, I Made Bagus; Tusta Adiputra, Putu Anda (E-Jurnal Medika Udayana; vol 2 no1 (2013):e-jurnal medika udayana, 2013)
Minor surgery is a general surgical procedure that applied with minimally invasive procedures and short duration, done in a superficial or just the affected tissue.  This technique is normally only requires a local anaesthetic and only has minimal  risk or complications. There are many cases that could be dealt with minor surgery one is veruka. Veruka or known as cutaneous warts is a disease that is often complained in children and adults. Veruka being estimated to occur until over 10% in children and young adults. Largest incident occurred in range of age 12 to 16 years. Veruka occurs more frequently in women than men. The peak incidence occur of age 13 years on women and 14.5 years in males. Salicylic acid and cryosurgery therapy are two of the most frequently performed in the treatment of cutaneous warts. Salicylic acid is therapy  for cutaneous warts who recently had already started replaced by cryosurgery because it is relatively easy to do and faster recovery.
Keywords: minor surgery, cutaneous warts, cryosurgery